Bounds of a Unified Integral Operator via Exponentially s, m-Convexity and Their Consequences. (22nd May 2020) - Hu, Yi; Farid, Ghulam; Zijiang; Mahreen, Kahkashan
Abstract : Various known fractional and conformable integral operators can be obtained from a unified integral operator. The aim of this paper is to find bounds of this unified integral operator via exponentially s, m -convex functions. The resulting bounds provide compact formulas for the bounds of associated fractional and conformable integral operators. Several Hadamard-type inequalities have been produced from a compact version for unified integral operators for exponentially s, m -convex functions.